Productivity enhancement and cycle time reduction in toyota production system through jishuken activity – Case study. (2021) - Ram Kumar, S.; Nimesh Nathan, V.; Mohammed Ashique, S.I.; Rajkumar, V.; Arun Karthick, P.
Abstract: The Toyota Production System (TPS) is a process widely used in manufacturing industries which deals with the waste management in firms. Jishuken is a form of problem solving technique which uses Kaizen combined with a Kaizen blitz, but it involves more than solving a problem. Some of the undesired activities that include non-value added movements, improper work floor arrangement, labour's activities ends in reduction of productivity rate. For such cases firms seeking ideal results which lasts for long term of period. In our project we implementing the principles of Toyota Production System in the firm by looking the problems involved in each activities by the process called Jishuken. We completed the time study for each processes of the firm and we collected the bottlenecks in each processes by Jishuken. The solutions we proposed are meant to be permanent which yield higher productivity rate when compared to the old setup. Here in our project we increased the productivity rate, and reduced the cycle time and operator's ideal time. We modified the arrangement of chutes in assembly line and increased the number of chutes, position of the torque gun is fixed, additional arrangements for pre testing of horns– stage before the final testing process to eliminate the number of reworking.